2019
DOI: 10.1037/dev0000660
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sequelae of mothers’ and fathers’ mind-mindedness in infancy: A developmental path to children’s attachment at age 10.

Abstract: Long-term sequelae of mothers' and fathers' mind-mindedness in infancy: A developmental path to children's attachment at age 10. Developmental Psychology, 55(4), 675-686.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 65 publications
(116 reference statements)
2
33
0
1
Order By: Relevance
“…Imitation is an important feature of human development because it is through imitation that we develop social cognition, which enables us to understand another’s thoughts and feelings and share our conscious experiences with one another. During development, early social interactions between mothers and infants help shape later socioemotional functions (Prochazkova and Kret, 2017 ; Miller et al, 2019 ). For example, during language acquisition in infants, mothers often speak in exaggerated tones and facial expressions to emphasize the sounds and movements of novel words, a behavioral phenomenon known as motherese (Nelson et al, 1989 ; Falk, 2004 ).…”
Section: Evolutionary Purpose Of Dance: Driving Interpersonal Coordinmentioning
confidence: 99%
“…Imitation is an important feature of human development because it is through imitation that we develop social cognition, which enables us to understand another’s thoughts and feelings and share our conscious experiences with one another. During development, early social interactions between mothers and infants help shape later socioemotional functions (Prochazkova and Kret, 2017 ; Miller et al, 2019 ). For example, during language acquisition in infants, mothers often speak in exaggerated tones and facial expressions to emphasize the sounds and movements of novel words, a behavioral phenomenon known as motherese (Nelson et al, 1989 ; Falk, 2004 ).…”
Section: Evolutionary Purpose Of Dance: Driving Interpersonal Coordinmentioning
confidence: 99%
“…For instance, maternal use of appropriate mindrelated comments while playing with their infant was longitudinally related to secure attachment, whereas inappropriate, nonattuned mind-related comments were not (Arnott & Meins, 2007;Meins et al, 2012). Similarly, Miller, Kim, Boldt, Goffin, and Kochanska (2019) demonstrated that appropriate MMM (and not nonattuned MMM) was longitudinally related to attachment security in middle childhood. In addition, these authors reported that the relation between appropriate MMM and secure child attachment in mothers was mediated by maternal responsiveness and infant attachment security, while in fathers mediation was only found for infant security.…”
mentioning
confidence: 94%
“…Meins et al (2001) define mindmindedness as "the mother's proclivity to treat her infant as an individual with a mind, rather than merely as a creature with needs that must be satisfied" (p. 638) [70]. A substantial body of research has demonstrated positive associations between parental mind-mindedness and child attachment [71][72][73], emotion regulation [74], and executive functioning [75,76], as well as maternal responsive feeding behaviors [77]. Given its import to multiple domains of child development, it seems judicious to test the extent to which different intervention approaches impact both mind-mindedness and weight status.…”
Section: Discussionmentioning
confidence: 99%